Prenatal exposure to the probiotic Lactococcus lactis decreases anxiety-like behavior and modulates cortical cytoarchitecture in a sex specific manner. - Natalia Surzenko; Eneda Pjetri; Carolyn A Munson; Walter B Friday; Jonas Hauser; Ellen Siobhan Mitchell (PLoS ONE, 2020)
Development of the cerebral cortex may be influenced by the composition of the maternal gut microbiota. To test this possibility, we administered probiotic Lactococcus lactis in drinking water to mouse dams from day 10.5 of gestation until pups reached postnatal day 1 (P1). Pups were assessed in a battery of behavioral tests starting at 10 weeks old. We found that females, but not males, exposed to probiotic during prenatal development spent more time in the center of the open field and displayed decreased freezing time in cue associated learning, compared to controls. Furthermore, we found that probiotic exposure changed the density of cortical neurons and increased the density of blood vessels in the cortical plate of P1 pups. Sex-specific differences were observed in the number of mitotic neural progenitor cells, which were increased in probiotic exposed female pups. In addition, we found that probiotic treatment in the latter half of pregnancy significantly increased plasma oxytocin levels in mouse dams, but not in the offspring. These results suggest that exposure of naïve, unstressed dams to probiotic may exert sex-specific long-term effects on cortical development and anxiety related behavior in the offspring.